2016
DOI: 10.1128/aem.00306-16
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Specific Features of Extracellular Polysaccharides and Their Impact on Lactobacillus plantarum-Host Interactions

Abstract: Lactobacilli are found in diverse environments and are widely applied as probiotic, health-promoting food supplements. Polysaccharides are ubiquitously present on the cell surface of lactobacilli and are considered to contribute to the species-and strainspecific probiotic effects that are typically observed. Two Lactobacillus plantarum strains, SF2A35B and Lp90, have an obvious ropy phenotype, implying high extracellular polysaccharide (EPS) production levels. In this work, we set out to identify the genes inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 63 publications
4
75
0
1
Order By: Relevance
“…Differences in the quantities and compositions of EPS among the strains are likely attributed to differing metabolic activities (43) or varied DNA compositions. For example, significant differences in EPS between parent and mutant strains have been reported in numerous studies (42,44,45) and support our conclusion of the strain-specific IR features of EPS. Moreover, glucose-yeast extract medium and the steady-growth stage of bacteria (48 h) were used for EPS formation and extraction in this work.…”
Section: Discussionsupporting
confidence: 91%
“…Differences in the quantities and compositions of EPS among the strains are likely attributed to differing metabolic activities (43) or varied DNA compositions. For example, significant differences in EPS between parent and mutant strains have been reported in numerous studies (42,44,45) and support our conclusion of the strain-specific IR features of EPS. Moreover, glucose-yeast extract medium and the steady-growth stage of bacteria (48 h) were used for EPS formation and extraction in this work.…”
Section: Discussionsupporting
confidence: 91%
“…Impact of EPSs on adhesion of L. gasseri DSM 14869 to different epithelial cells. Previous studies have shown that EPSs from intestinal lactobacilli are involved in adhesion to intestinal epithelial cells (16,18,19). In this study, we investigated the role of EPSs in the adhesive capacity of the vaginal strain L. gasseri DSM 14869.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial polysaccharides vary in sugar composition, position of branches, and modifications, contributing to the wide diversity of surface structures (15). EPSs have been reported to be involved in aggregation, biofilm formation, adhesive properties, and immunomodulation by probiotic strains (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…The procedures of microorganisms by which they act as probiotics or do their effects are not properly known, but the many studies revealed that they may be involved in modifying the pH value, may neutralize the pathogens through production of compounds that exerts property of antimicrobial, and may occupy the receptor sites of the pathogens as well as chase them for available nutrient [123]. The role of functional food which includes the probiotics microorganisms in human health is well known.…”
Section: Beneficial Microbes For Human Healthmentioning
confidence: 99%